The Effect of the Financial Crisis on the Taxation of Consumption, Labour, and Capital in the European Union - Krajewska, Anna (Comparative Economic Research. Central and Eastern Europe, 2013)
The impact of the current financial crisis on changes in the taxation of consumption, labour, and capital in the European Union. The responses reflected in the tax policies pursued in the EU countries to the current crisis will be analysed in three ways: 1. Distribution of total tax burden by economic function, i.e. assessment of the share of taxes on consumption, labour, and capital in relation to GDP and total tax revenues. Therefore, the analysis will cover backward-looking ta Xburden indicators; 2. Analysis of trends in the implicit tax rate (ITR) on consumption, labour and capital. The ITR is an indicator which expresses the relation of tax burdens levied on different activities to total revenue from this activity. The ITR takes into account the legislation and the resulting tax burden(s) which may affect the behaviour of various entities and their decisions. This approach is described as forward-looking effective tax rate; 3. Trends in the EU countries are compared with the changes taking place in Poland. This includes an explanation of the specificity of the fiscal policy pursued in Poland. 4. For the purpose of this paper we used statistics prepared according to the methodology adopted by the European Commission, published in “Taxation trends in the European Union”, Eurostat 2012.